MARKETING STRATEGIES OF INCREASING THE EXPORT CAPACITY OF COTTON-TEXTILE CLUSTER (Marketing Journal, 2025)
The study examined the role of marketing strategies in enhancing the export potential of cotton -textile clusters. It was identified that to improve export performance under increasing global competition, actions such as brand promotion, adoption of e - comme rce, product certification, and logistics optimization were essential. The research also emphasized the importance of understanding foreign market demands, conducting marketing analysis, and developing customer -oriented strategies. Based on 538 the findings, practical recommendations were formulated to support the advancement of cluster effectiveness and competitiveness.
Keywords: textile; cluster; export; export potential; management; standard